THE ROLE OF NEUROHUMORAL DYSFUNCTION IN PATHOGENESIS OF THE TRAUMATIC OPTIC NEUROPATHY - Мойсеєнко Н. М. (World of Medicine and Biology, 2017)
The neurohumoral properties’s changes in the hypothalamus as a result of TON are unknown. The purpose of the study: to study neurohumoral dysfunction in the traumatic optical neuropathy’s pathogenesis. Methods. The traumatic damage to the orbital part of the right optic nerve was reproduced in 60 sexually mature rabbits in the experiment. There were two groups of animals of 30 individuals: intact and experimental. Electronic microscopy of the hemithin and ultrathin sections and the morphometry of the cranial part of the right optic nerve and the suprachismic nucleus of the hypothalamus one month after the injury. It has been established that traumatic damage to the orbital part of the optic nerve causes reactive edema and destructive changes in the cranial part of the optic nerve and the suprachiasmic nucleus of the hypothalamus. The reducing the volumetric neurosecretory granules density and the pycnomorphic cells’ number at the last stage of development increasing were detected. This reduces the corticosteroids production that cause inflammatory reactive damage to the optic nerve. Conclusion. Hence, neurohumoral dysfunction is an important mechanism for the pathogenesis of traumatic optical neuropathy, and its correction will have positive effects for treatment.
Keywords: traumatic optical neuropathy; neurohumoral dysfunction; suprachiasmic nucleus of the hypothalamus; neurosecretory granules